Phytochemical Analysis, in vitro Antioxidant and Antidiabetic Activities of Different Solvent Fractions of Maytenus heyneana Root - G. Sumithira; G. P. Senthil Kumar; B. Krishnamoorthy; R. Suresh (Novel Aspects on Pharmaceutical Research Vol. 5, 2023)
Oxidative stress plays an important role in pathogenesis of chronic disease especially CVS disease (CVD), diabetes, cancer, neurodegenerative disease hence, the growing interest in the use of natural antioxidants as therapeutic tools exists. The aim of this study was to explore herbal drug which may become useful in the prevention of diabetes and antioxidant potential from ethanol extracts of Maytenus heyneana (MH) root belonging to the family Celastraceae and their different fractions were studied. Ethanolic extract of Maytenus heyneana root was fractionated into chloroform, ethyl acetate, and methanol by liquid-liquid extraction. The preliminary phytochemical analysis was done by standard methods to identify the presence of important compounds. In vitro antioxidants activities were carried by 2,2-diphenyl- 2-picrylhydrazyl (DPPH) and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) cation radical scavenging assays. For antidiabetic potential, \(α\)-amylase and \(α\)-glucosidase enzyme inhibitory studies were carried on different fractions. The qualitative phytochemical study on the different solvent fractions of the roots of MH showed the presence of some secondary metabolites such as cardiac glycosides, phenols, flavonoids, and terpenoids in all the fractions. Alkaloid was detected only in chloroform and ethyl acetate fractions and saponins were present only in methanol fraction. The presence of tannins was detected in ethyl acetate and methanol fractions except in chloroform fraction. However, steroids and proteins were absent in all the fractions. From the results of two assays prominent that at high concentration, methanolic fraction showed superior activity than the other two fractions, although among the different fractions, the methanol fraction showed significant increase in \(α\)-amylase activity (3.14 \(μ\)g/ml) when compared to the standard acarbose (4.67 \(μ\)g/ml) (p<0.05). it can be concluded that the methanol fraction of MH root could be a good candidature for further studies and the isolation of active phytoconstituents which is responsible in the management of diabetic and as antioxidant.